Pola Relasi Gender dan Kehidupan Sosial Ekonomi dalam Keluarga Buruh Perempuan di Jember (Studi Kasus pada Buruh Perempuan di Desa Panti Jember): Gender Relations Patterns and Socio-Economic Life in Female Laborer Families in Jember (A Case Study of Female Laborers in Panti Village, Jember) - Dwi Puspitarini (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
In general discourse, it is impossible to discuss